A Barbie no Instagram: os simulacros de intera????o da idealiza????o feminina - Silva, Ros??ngela Barbosa da (2016)
This thesis proposed to analyze what is happening in the context of verbal and non verbal communication process Barbie on Instagram. And the configuration of the expression plane and doll content plan that began to appeal not only to fashion costumes, the media agenda of the mass media to make sense, but he held on goal. The method that we used in this research is supported by the approach anchored in semiotics, more specifically in the French semiotics with structuralist basis, which includes not only the analysis of the written text, but understands the text in all its dimensions. The basis of the method developed in the postulates of Louis Hjelmslev. Barbie announces to its followers through Instagram, your style of life pleasing to the eyes of those who see. The doll on social media reveals the production of language. In cyber space, senses and values become infinite. Doll took for himself a space in social media in which she reveals a constructed and articulated reality. This shows that Barbie is also a reflection of the customs of an era, its evolution, its revolution. Including social and cultural aspects. At the end, we concluded that Barbie was created mediaticamente. It is a symbolic and discursive construction.